Structural Transformation and Employment Quality in Developing Countries Between Economic Growth and Social Inequality - Syarma, Ruth (Yayasan Cinta Negara Indonesia, 2025)
Structural transformation is an important process in the economic development of developing countries, characterized by the shift of labor from the traditional sector to the modern sector. This article analyzes how structural transformation affects the quality of employment, focusing on indicators of work formality, wages, social security, and productivity. Based on panel data from several developing countries between 2000 and 2022, it is found that despite a large shift of labor to the industrial and service sectors, improvements in employment quality do not always follow. Institutional factors, education, and labor policies are key in ensuring that structural transformation yields inclusive benefits